2018
DOI: 10.1002/jcp.27791
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine prevents pressure overload‐induced cardiac hypertrophy and heart failure by restoring aberrant Na+ and Ca2+ handling

Abstract: Background Cardiac hypertrophy and heart failure are characterized by increased late sodium current and abnormal Ca2+ handling. Ranolazine, a selective inhibitor of the late sodium current, can reduce sodium accumulation and Ca 2+ overload. In this study, we investigated the effects of ranolazine on pressure overload‐induced cardiac hypertrophy and heart failure in mice. Methods and Results Inhibition of late sodium current with the selective inhibitor ranolazine suppressed cardiac hypertrophy and fibrosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Additionally, it was previously shown that laminopathic cardiomyocytes are highly sensitive to apoptosis ( Ho et al, 2011 ; Lee et al, 2017 ), which could over the years contribute to the development of severe cardiac fibrosis that is typical in cardiac laminopathy patients ( van Tintelen et al, 2007b ; Fontana et al, 2013 ; Tobita et al, 2018 ). A corollary of these intriguing hypotheses is that medical interventions during the early phases of the disease, such as the use of calcium antagonists (such as our use of verapamil here) and/or anti-apoptotic agents ( Lee et al, 2014 ; Nie et al, 2018 ), may be able to prevent the development of heart failure in cardiac laminopathy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was previously shown that laminopathic cardiomyocytes are highly sensitive to apoptosis ( Ho et al, 2011 ; Lee et al, 2017 ), which could over the years contribute to the development of severe cardiac fibrosis that is typical in cardiac laminopathy patients ( van Tintelen et al, 2007b ; Fontana et al, 2013 ; Tobita et al, 2018 ). A corollary of these intriguing hypotheses is that medical interventions during the early phases of the disease, such as the use of calcium antagonists (such as our use of verapamil here) and/or anti-apoptotic agents ( Lee et al, 2014 ; Nie et al, 2018 ), may be able to prevent the development of heart failure in cardiac laminopathy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic or intracellular Ca 2+ overload and exhausted Ca 2+ stores disturb protein folding, leading to an unfolded protein response and endoplasmic reticulum (ER) stress (Hayashi and Su 2007). In the failing heart, ER-initiated stress has been reported to contribute to cardiomyocyte apoptosis (Nie et al 2019). Intracellular Ca 2+ overload within cardiomyocytes may be involved in the transition from adaptive cardiac hypertrophy to pathological cardiac hypertrophy.…”
Section: Development Of Intracellular Calcium Overloadmentioning
confidence: 99%
“…Along with the effects of cytosolic Ca 2+ overload previously discussed, intracellular Ca 2+ overload within cardiomyocytes contributes to the activation of pro-hypertrophic signaling pathways that stimulate the progression of pathological cardiac hypertrophy. Elevated levels of intracellular Ca 2+ lead to increased binding of Ca 2+ with inactive calmodulin (CaM) to form active CaM (Nie et al 2019). Active CaM initiates signaling pathways involving Ca 2+ /CaM/CaMKII/myocyte enhancer factor-2 (MEF-2) and Ca 2+ /CaM/CaMKII/calcineurin/nuclear factor of activated T-cells (NFAT), which are pro-hypertrophic signaling pathways (Zhang et al 2007).…”
Section: Development Of Intracellular Calcium Overloadmentioning
confidence: 99%
“…Late Na + current, through the actions of the sodium Ca 2+ exchanger, may impact intracellular Ca 2+ , contributing to further activation of CaMKII as well as driving the incidence of arrhythmogenic DADs. Ranolazine has been used successfully in rodents and large animals to block these changes and prevent the development of hypertrophy, HF, and arrhythmias (Rastogi et al, 2008;Figueredo et al, 2011;Glynn et al, 2015;Liang et al, 2016;Ellermann et al, 2018;Nie et al, 2019). However, results from clinical trials have been mixed with data supporting that ranolazine is safe with questionable efficacy in preventing AF recurrence (RAFAELLO trial), ventricular tachycardia (VT) or ventricular fibrillation (VF) following implantation of cardioverter defibrillator (RAID trial), or improving functional capacity in hypertrophic cardiomyopathy (RESTYLE-HCM trial) (De Ferrari et al, 2015;Bengel et al, 2017;Olivotto et al, 2018;Zareba et al, 2018).…”
Section: Therapeutic Targeting Of the Camkii Signaling Pathwaymentioning
confidence: 99%